MODEL PENANGANAN ANAK BERKESULITAN BELAJAR SPESIFIK KARENA FAKTOR DISFUNGSI MINIMAL OTAK (DMO) DI SEKOLAH DASAR - Haryanto, Haryanto (LPMPP Universitas Negeri Yogyakarta, 2003)
This article is based on a research conducted to (I) identifY elementary schoolchildren suspected ofhaving specific leaning difficulty caused by minimal dysfunction of the brain and (2) determine a model ofthe teacheraction to deal with itand the effect ofits intervention onthe effort to increase these children's learning achievement The research was conducted in Gamping, Sleman, using multi-stage sampling having two stages. Atstage one, ten out offorty elementary schools in the region were selected for the research. Atstage two, children inthe second and third grades were selected as research subjects. The data were obtained by means ofobserva tions, interviews, and demonstrations by the research team and the class teachers. The results and conclusions ofthe study indicate that forty-five (or 8.60 %) ofthe 523 second- and third-grade students ofthe ten elementary schools have specific learning difficulties in mathematics, thirty-six (or 6.30 %) ofthem have writing difficulties, thirty-three (or 6.30 %)ofthem have reading difficulties, and twenty (or3.82 %)ofthem have difficulties with skills and orientation.